Age-Related Changes in the Association Between Traumatic Brain Injury and Dementia in Older Men and Women. Issue 3 (May 2021) - Jacob, Louis; Azouvi, Philippe; Kostev, Karel
Abstract : Objective: To investigate age-related changes in the association between traumatic brain injury (TBI) and dementia in older men and women separately. Setting: A total of 243 general practices in the UK. Participants: This study included 4760 patients who received a first TBI diagnosis between 1995 and 2010 (index date), and 4760 patients without TBI who were matched to those with TBI by age, sex, index year, Charlson Comorbidity Index, alcohol dependence, and physician (index date: a randomly selected visit date). Design: Retrospective cohort study. Main measures: Incidence of dementia in the decade following index date. Results: Within 10 years of index date, 8.8% of men with TBI and 4.8% of those without TBI were diagnosed with dementia, while the respective figures were 9.0% and 6.7% in women ( P values < .01). There was a significant association between TBI and dementia in men (hazard ratio [HR] = 2.29, 95% confidence interval [CI]: 1.64-3.19) and in women (HR = 1.33, 95% CI: 1.07-1.64). Furthermore, the association between TBI and dementia was significant in men aged 60 to 70 (HR = 2.51, 95% CI: 1.27-4.96) and 71 to 80 years (HR = 3.00, 95% CI: 1.82-4.93), whereas the relationship was only significant and potentially unreliable in women aged 81 to 90 years (HR = 1.49, 95% CI: 1.03-2.14). Conclusions: The age-related relationship between TBI and dementia differed between men and women. More research of a prospective nature and including behavioral data is needed to better understand these differences.